REKSADANA SYARIAH dan KONVENSIONAL DI INDONESIA - Adhi, Nurseto; Aji, Dewi Pratiwi; Winarni, Winarni (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2021)
This study aims to test the difference between the conventional mutual fund and the sharia mutual fund on performances and risk. The development of mutual fund products is based on 2 (two) categories, conventional mutual funds, and sharia mutual funds (www.ojk.go.id). Based on data from the Data Center and Statistics of Islamic Mutual Funds, the performance of Islamic mutual funds is still underperformed compared to conventional mutual funds. Therefore, testing the performance of Islamic mutual funds by testing the performance of conventional mutual funds has not been widely tested. Secondary data was used in this study with all 1425 mutual funds from 2012-2017 on the Indonesia Stock Exchange was used as the population in this study is. The purposive sampling technique determines the sample in this study. The sample used in this study was Conventional and Shariah mutual fund in Indonesia Stock Exchange (IDX) with six products each. This hypothesis test used Differential Test tools with data analysis techniques using Paired sample t-test analysis using SPSS 25. In this study, we found that there was a significant difference between the return on conventional mutual funds and Syariah mutual funds. While the risk, Sharpe method, Treynor method, and Jensen method have not significant difference between conventional mutual funds and Syariah mutual funds.